Wartawan Media Now dalam Mengemas Berita: Perspektif Situational Theory - Dasrun Hidayat; Anisti Anisti (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2015)
The study aims to map and describe relationships between concepts of activity of journalists in the media now cloning technology based activities and relationship between news reporters. This study discusses the focus of news coverage in media activities and relationships among the journalists in the era of technology. The theory used is situational theory Grunig and Hunt and descriptive method of Public Relations. The study found that the situation changes in the era of media encourage actions of unscrupulous hunters cloning news. News media such as online media should now be used as the initial data is not the primary data news writing. The presence of media now facilitates the work of journalists but not always produce good quality of news. Otherwise, the presence of technology encourages more active cloning news reporter. Media now can initiate active and apathetic public situations as influenced by quality news content. The presence of media technology changes the image of the relationship between journalists—from person to person or reporter to reporter to journalists with media technology.